2015
DOI: 10.1164/rccm.201504-0818oc
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Pulmonary Fibrosis in United States Automated Claims. Incidence, Prevalence, and Algorithm Validation

Abstract: Sensitive algorithms without correction for false positive errors overestimated incidence and prevalence of IPF. An IPF score offered the greatest PPV, but it requires further validation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
71
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(87 citation statements)
references
References 25 publications
5
71
1
3
Order By: Relevance
“…They found no significant difference in the distribution of patient demographics and clinical characteristics between the subsample and the database population [23], thus validating the proper selection of IPF patients using this code. Very recently, a study presented another method to assess the performance of algorithms applied to identify IPF patients including validation by calculating positive predictive value using medical records [27]. This approach, which may be more accurate, could not be applied in our study, due to the difficulty of obtaining nominative patient-level data in France.…”
Section: Discussionmentioning
confidence: 99%
“…They found no significant difference in the distribution of patient demographics and clinical characteristics between the subsample and the database population [23], thus validating the proper selection of IPF patients using this code. Very recently, a study presented another method to assess the performance of algorithms applied to identify IPF patients including validation by calculating positive predictive value using medical records [27]. This approach, which may be more accurate, could not be applied in our study, due to the difficulty of obtaining nominative patient-level data in France.…”
Section: Discussionmentioning
confidence: 99%
“…First, there is debate on how to identify IPF patients using claims data. The ICD-9-CM code we used has been used before in several publications [1, 6, 23, 24], however a recent validation study (not in the NIS) found it had a positive predictive value of 30-60% [29]. While less than desirable, this positive predictive value is within the range reported in study of ICD-9-CM codes for 32 conditions (median 80.7%, mean 77%, range 23-100%) [30].…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological data for IPF can vary widely due to variations in the data collection methods and classification terms used (table 1) [11,12]. Throughout Europe and North America, the estimated incidence of IPF has been reported to range between 2.8 and 19 cases per 100 000 people per year [23][24][25].…”
Section: Introductionmentioning
confidence: 99%